ISOLATION OF AEROBIC AND ANAEROBIC BACTERIA IN TRANSIENT BACTEREMIA - CHITRA.N; V.MANGAYARKARASI (International Journal of Pharma and Bio Sciences, 2015)
The normal oral cavity has a large and diverse resident microflora. These microorganisms are generally considered non-pathogenic and as normal inhabitants of the oral cavity. Bacteremia in dentistry frequently occurs due to entry of these bacteria into the bloodstream following procedures such as periodontal probing, root canal treatment, orthodontic treatment, and oral hygiene procedures. Invasive procedures such as extractions, periodontal surgery and third molar surgery pose a higher risk of causing bacteremia. In a healthy person, bacteremia in the bloodstream is transient in nature and is countered by normal defense mechanisms. However, bacteremia may cause infective endocarditis (IE) in patients with cardiac anomalies or in immunocompetent or immunocompromised patients. The aims of this study were to isolate and identify the various types of aerobic and anaerobic bacteria causing transient bacteremia after third molar surgery and to find their prevalence.